Pressure-induced metallization and 3d-like behavior in TcS2. Issue 46 (19th May 2022) - Sayre, Dean; Siska, Emily; Smith, G. Alexander; Chang, Nicholas; Park, Changyong; Poineau, Frederic; Schwartz, Craig P.; Lawler, Keith V.; Salamat, Ashkan
Abstract : TcS2 metallizes through interlayer interactions when sufficiently dense and has a high pressure extended 3D phase similar to MnS2 . Abstract : TcS2 undergoes a charge transfer insulator to metal transition above 28 GPa. Laser annealing reveals a kinetically hindered high pressure arsenopyrite phase that is recoverable to ambient. The new phase is similar to the Mn-dichalcogenides rather than the expected Re-dichalcogenides and involves the formation of S–S and Tc–Tc bonds.